P-037 Prevalence and Detection of Sporadic Adenomas in IBD Patients. (March 2016) - Baig, Kamal; Chablaney, Shreya; Caldis, Matthew; Alabbas, Bedoor; Wazzem, Mohammed; Dougherty, Timothy; Borum, Marie
Abstract : Background: Patients with Inflammatory Bowel Disease (IBD) are at risk for dysplasia and colorectal cancer (CRC) related to underlying chronic inflammation. Similar to the general population, individuals with IBD are at risk for sporadic adenomas that may also progress to CRC. Benchmark adenoma detection rates (ADR) in average-risk patients are 15% in women and 25% in men. ADR benchmarks have not yet been established for IBD patients. The frequency of surveillance colonoscopies may complicate the establishment of accurate ADR in IBD patients. This study evaluated the prevalence of sporadic adenomas in an average-risk population and in IBD patients at a university medical center. Methods: A retrospective medical record review of average-risk and IBD patients undergoing a colonoscopy at a university medical center during a 1-year period was conducted. Records of IBD patients were also examined to determine whether colonoscopies had been performed during the previous 5 years. Maintaining patient confidentiality, a database of demographic, clinical, colonoscopic, and pathologic information was created in Microsoft Excel. Statistical analysis was performed using Fisher's Exact Test with significance set at P < 0.05. The study was approved by the university institutional review board. Results: There were 1523 patients who had an average-risk screening colonoscopy. There were 656 females and 867 males, with an average age of 57.9 years (95% confidence interval of 57.1–58.7). Six hundred thirty-three patients (41.6%) had an adenoma detected. There were 136 IBD patients had a surveillance colonoscopy. Among IBD patients, 29 (21.3%) had one or more procedures during the previous 5 years. There were 20 females and 9 males with an average age of 51.0 years (95% confidence interval 44.8–57.2). Sporadic adenomas were detected in 7 (24.1%) of these patients. There was no significant difference ( P = 0.0848) in the ADR of average risk individuals and IBD patients. Conclusions: While IBD patients are at risk for IBD-related dysplasia, sporadic adenoma is also possible. The adenoma detection rate (ADR) benchmarks, a quality indicator for screening colonoscopies, are not yet available for IBD surveillance procedures. This study exposed a trend toward a lower incidence of adenoma in IBD patients compared to the general population. This might reflect a slightly younger population of IBD patients, an IBD-related alteration in neoplastic pathways, or an effect of IBD medications stabilizing the mucosa. However, the results of this study are limited due to small sample size and single institutional design. Further study is needed to determine the incidence of adenomas and to establish ADR benchmarks for quality procedures in IBD patients.